2018 Vegetable Production Handbook Chapter 14: Potato Production - Lincoln Zotarelli; Peter J. Dittmar; Pamela D. Roberts; Johan Desaeger; Joseph W. Noling; Bonnie Wells (EDIS)
This 21-page fact sheet is chapter 14 of the 2018 Vegetable Production Handbook. Written by Lincoln Zotarelli, Peter J. Dittmar, Pamela D. Roberts, Johan Desaeger, Joseph W. Noling, and Bonnie Wells, and published by the Horticultural Sciences Department, 2018.